2013
DOI: 10.1111/cdev.12097
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation and Transfer of Learning After Observing Hand Gesture

Abstract: Children who observe gesture while learning mathematics perform better than children who do not, when tested immediately after training. How does observing gesture influence learning over time? Children (n = 184, ages = 7-10) were instructed with a videotaped lesson on mathematical equivalence and tested immediately after training and 24 hr later. The lesson either included speech and gesture or only speech. Children who saw gesture performed better overall and performance improved after 24 hr. Children who on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(190 citation statements)
references
References 48 publications
8
148
0
9
Order By: Relevance
“…These findings are expected given similar findings using live and prerecorded stimuli [9], [10], [6]. However, these findings go beyond prior work in that they provide more convincing evidence that the effect observed is due to hand gesture rather than to some associated confound.…”
Section: B Study 2: Do Instructor Gestures Promote Learning?supporting
confidence: 79%
See 1 more Smart Citation
“…These findings are expected given similar findings using live and prerecorded stimuli [9], [10], [6]. However, these findings go beyond prior work in that they provide more convincing evidence that the effect observed is due to hand gesture rather than to some associated confound.…”
Section: B Study 2: Do Instructor Gestures Promote Learning?supporting
confidence: 79%
“…In addition to facilitating initial learning, gesturing during mathematics instruction also makes it more likely that children will retain their new learning over time, above and beyond the amount of retention shown by children who learn the same amount without gesture, and increases transfer of knowledge to novel contexts [10]. Gesture is a spontaneous behavior that is routinely incorporated into human communication, and so it is perhaps not surprising that it is generally helpful for listeners.…”
Section: Prior Workmentioning
confidence: 99%
“…Observing others' movements could support episodic memories as encoding of the words relied on the context or the situation elements. Moreover, numerous studies have shown that observing gestures can have positive effects on learning (e.g., Church, Ayman-Nolley, & Mahootian, 2004;Cook, Duffy, & Fenn, 2013;Ping & Goldin-Meadow, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…A second suggestion is that aphasic patients may compensate auditory comprehension deficits with additional nonverbal information deriving from the actors' co-speech gestures and therefore may fixate more the speaker's co-speech gestures, i.e., the hands. There is evidence that the presence of co-speech gestures improves information encoding and memory consolidation (Cohen & Otterbein, 1992;Cook, Duffy, & Fenn, 2013;Feyereisen, 2006;Records, 1994). Finally, the third suggestion is based on the cognitive processing view: Aphasic patients allocate their limited attentional resources (Kahneman, 1973) on the auditory input and avoid competing input from visual speech perception.…”
Section: Introductionmentioning
confidence: 99%